Fecal Bile Acids Profile of Crewmembers Consuming the Same Space Food in a Spacecraft Simulator - Dong, Hai-Sheng; Shen, Qi-Bing; Lan, Hai-Yun; Zhao, Wei; Cao, Ping; Chen, Pu (Frontiers in Physiology, 2021)
Introduction: Recently, bile acids (BAs) are increasingly being considered as unique metabolic integrators and not just for the cholesterol metabolism and absorption of dietary lipids. Human BAs profiles are evolved to be individual under different environmental, dietary, and inherited factors. Variation of BAs for crewmembers from freshly prepared kitchen diets to wholly prepackaged industrial foods in a ground-based spacecraft simulator has not been clearly interpreted. Methods: Three crewmembers were confined in a docked spacecraft and supplied with 7 days periodic wholly prepackaged industrial foods for 50 days. Fecal samples were collected before entry in the spacecraft simulator and after evacuation. Determination of 16 kinds of BAs was carried out by high-performance liquid chromatography tandem mass spectrometry method. Results: Bile acids metabolism is sensitive to diet and environment transition from freshly prepared kitchen diets in the canteen to wholly prepackaged industrial foods in a ground-based spacecraft simulator, which is also specific to individuals. A significant positive relationship with a coefficient of 0.85 was found for primary BAs as chenodeoxycholic acid (CDCA) and cholic acid (CA), and a significantly negative relationship with a coefficient of −0.69 for secondary BAs as lithocholic acid (LCA) and deoxycholic acid (DCA). Discussion: The profile of BA metabolism of individuals who share the same food in the same environment appears to be unique, suggesting that the inherent ability of different individuals to adapt to diet and environment varies. Since the transition from the free diet in open space to whole prepackaged space food diet in a space station simulator causes the variations of BAs pool in an individual manner, assessment of BA metabolic profiles provides a new perspective for personalized diet design, astronaut selection and training, and space flight diet acclimatization.